Circumvallate Placenta: Associated Clinical Manifestations and Complications—A Retrospective Study. (13th November 2014) - Taniguchi, Hanako; Aoki, Shigeru; Sakamaki, Kentaro; Kurasawa, Kentaro; Okuda, Mika; Takahashi, Tsuneo; Hirahara, Fumiki
Abstract : Aims. To analyze the pregnancy outcomes of circumvallate placenta retrospectively and to predict circumvallate placenta during pregnancy based on its clinical features. Methods. The pregnancy outcomes of 92 women with circumvallate placenta who delivered live singletons at a tertiary care center between January 2000 and September 2012 were compared with those of 9057 controls. Results. Women with circumvallate placenta were associated with higher incidences of preterm delivery (64.1%), placental abruption (10.9%), emergency cesarean section (45.6%), small-for-gestational age (36.9%), neonatal death (8.9%), neonatal intensive care unit admission (55.4%), and chronic lung disease (33.9%). When vaginal bleeding during the second trimester and premature chemical rupture of membranes (PCROM) were both used as predictive factors for circumvallate placenta, the sensitivity was 28.8% and specificity was 99.9%. Conclusion. With circumvallate placenta, pregnancy outcomes were poor and had characteristic clinical manifestations. In women with both vaginal bleeding and PCROM during pregnancy, circumvallate placenta should be strongly suspected.